Analisis Korpus Bahasa Tentang Nilai Kepemimpinan KH Ahmad Dahlan Dalam Pidato Kepemimpinan Muhammadiyah Kontemporer - Primandhika, Restu Bias; Mulkhan, Abdul Munir; Sari, Zamah (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
This study aims to analyze the representation of KH Ahmad Dahlan's leadership values in contemporary Muhammadiyah speeches using corpus linguistic analysis. The data analyzed consisted of a corpus from KH Ahmad Dahlan's leadership texts and transcriptions of contemporary Muhammadiyah leaders' speeches. Corpus linguistic analysis was employed as the analytical method, supported by Python programming language on Google Colab utilizing several libraries such as the Natural Language Toolkit (nltk) and Sastrawi. The word frequency analysis revealed that in KH Ahmad Dahlan's text corpus, the words "orang" (n=156), "islam" (n=151), and "agama" (n=70) dominated, reflecting a focus on education and character development. In contrast, contemporary Muhammadiyah speeches highlighted words like "indonesia" (n=174), "bangsa" (n=108), and "negara" (n=101), indicating a shift towards nationalism and statehood issues. Trigram collocation analysis using Pointwise Mutual Information (PMI) further supports these findings. For example, the phrase "islam ajar amal" (PMI: 4.85) in KH Ahmad Dahlan's era shifted to "islam dinul haqq" (PMI: 4.98) in the contemporary era. Additionally, the collocation "bangsa satu umat" (PMI: 4.12) transitioned to "bangsa merdeka adil" (PMI: 4.98), reflecting the strengthening of nationalistic narratives. These findings demonstrate that Muhammadiyah has successfully adapted KH Ahmad Dahlan's core values to remain relevant amid current social and global challenges.